EVALUATION OF POD SHATTERING RESISTANCE AND AGRONOMIC PERFORMANCE OF SEVERAL SOYBEAN PROMISING LINES - Ayda Krisnawati; M Muchlish Adie; Dotti Suryati (BERITA BIOLOGI, 2020)
Pod shattering is one of the sources of yield losses during soybean cultivation in Indonesia. This research aimed to identify the resistant genotypes to pod shattering and the performance of its agronomic characters. The field study was conducted in the dry land of South Lampung from May to August 2017 using twelve soybean genotypes. The experiment was arranged in a randomized block design with four replicates. The observation of pod shattering was using oven-dry and sun-drying methods. The result showed that a rise temperature of oven increased the pod shattering. The rates of shattering on oven temperature of 30 °C, 40 °C, 50 °C, and 60 °C were of 0, 8.26%, 46.13%, and 51.06%, respectively. The rate of shattering of oven-dry method at 60 °C ranged from 3.62 – 87.23%. On the sun-drying method, the rate of shattering after 15 days treatment was ranged from 0 – 67.36%. The screening for pod shattering by using the oven-dry method has successfully obtained two resistant varieties to pod shattering (Anjasmoro and G511H/Anj-1-3), whereas by using the sun-drying method there were three resistant genotypes (Anjasmoro, G511H/Anj-1-3, G511H/Anjasmoro-1-4). The evaluation of shattering resistance using oven-dry method resulted in a higher pressure than those of by sun-drying method. The Anjasmoro variety and G511H/Anj-1-3  showed consistent resistance to pod shattering by both methods. The G511H/Anj-1-3produced high yield, have large seed size and early days ofmaturity. Thus, the G511H/Anj-1-3was potentially be developed in Indonesiaand other tropical regions. The availability of a high yield and shattering resistant genotype will be beneficial to increase soybean productivity.